Goat manure fertilization effect on saponin and protein content in quinoa (chenopodium quinoa willd) grain of different origin - González, Juan Antonio (2020)
Background and objectives: A field experiment using two quinoa varieties (Regalona Baer andCICA) was performed to determine the effects of goat manure fertilization on saponin and proteingrain content was performed. A trial was conducted in a valley at 2,000 m a.s.l (Tucumán, Argentina)and at different levels of goat manure addition equivalent to 0, 32, 64, 128, 192 kg N/ha.Findings: Saponin and protein content increased almost linearly as goat manure fertilizationincreased. However, there was a varietal difference, R. Baer synthesized more saponin than CICA atthe same nitrogen level. Conclusions: The study indicated that the quinoa saponin content, in absenceof water stress and salinity, but under the same agronomical managements, increased linearly withgoat manure addition. Probably the differences in response to fertilization of both varieties wererelated to the genotypes origin, one from high mountain (CICA) and the other from lowland (R. Baer).Significance and novelty: Goat manure fertilization on quinoa produced more proteins but thesaponin synthesis increased in the same way. Additionally, quinoa varieties showed variability for thesaponin content. Thus, it is necessary to found an equilibrium point to produce a grain for humanconsumption with high protein and low saponin content or a grain with high protein and high saponincontent for a later industrial separation of both compounds